Direct AC-AC Propulsion System Using Matrix Converter and 5Φ Traction Motor for HEV Vehicle - Dobrucký, Branislav; Kascak, Slavomir; Prazenica, Michal; Pavlasek, Pavel (Communications - Scientific letters of the University of Zilina, 2018)
The paper deals with direct AC-AC propulsion system using [nx5] matrix converter and five-phase traction induction motor (IM) for hybrid electric vehicle (HEV) including electronic differential. Using the direct AC-AC system, in comparison to classical rectifier-inverter with DC link, features smaller on-state semiconductor switches losses and consequently higher efficiency of power train of the vehicle. The major advantage of using a five-phase machine instead of three-phase one is in smaller torque pulsation and better fault tolerance under one phase of supply. There are presented comparative analyses of [3x5], [5x5], [2x5], [1x5], [0x5] matrix converter feeding five-phase induction motor for HEV vehicle. Modeling and simulation are done using Matlab-Simulink environment, and simulation experimental results are given in the paper.